Increasing Environmental Awareness Through Waste Bank And Technology Wastewater Treatment Plant (WWTP) Osowilangon Benowo Tambak Surabaya - Abdullah, M. Hasan; Subaderi, Subaderi; Gemala Dewi, Fitriya (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2022)
A healthy living environment is a necessity for the community. However, public awareness of these needs is not in accordance with reality. The problem of waste and household waste water sanitation is an unresolved problem. The service program through Real Work Lectures (KKN) was carried out in RW 04, Tambak Osowilangon village. This activity was carried out by providing information on the procedures for establishing a waste bank and making healthy and inexpensive WWTP technology. The form of this service program is the growth of public awareness to maintain personal and environmental health. The community can manage waste in a modern way through a waste bank and have an WWTP that is safe for the environment.